Geospatial metadata retrieval from web services - Barbosa,Ivanildo (2013)
Nowadays, producers of geospatial data in either raster or vector formats are able to make them available on the World Wide Web by deploying web services that enable users to access and query on those contents even without specific software for geoprocessing. Several providers around the world have deployed instances of WMS (Web Map Service), WFS (Web Feature Service) and WCS (Web Coverage Service), all of them specified by the Open Geospatial Consortium (OGC). In consequence, metadata about the available contents can be retrieved to be compared with similar offline datasets from other sources. This paper presents a brief summary and describes the matching process between the specifications for OGC web services (WMS, WFS and WCS) and the specifications for metadata required by the ISO 19115 - adopted as reference for several national metadata profiles, including the Brazilian one. This process focuses on retrieving metadata about the identification and data quality packages as well as indicates the directions to retrieve metadata related to other packages. Therefore, users are able to assess whether the provided contents fit to their purposes.